The Influence of Destination Image on Revisit Intention: The Moderating Impact of Electronic Word of Mouth Marketing (eWOM) - Ching, Jia Lie (Universiti Malaysia Sarawak (UNIMAS), 2021)
In this emerging digitalised ecosystem, ecotourism is one of the significant motivators in tourism and the government has set their goals to enhance ecotourism development as proposed by the Visit Truly Asia Malaysia 2020 campaign. In addition, the growth of destination image should be developed in a way that could increase the tourists’ revisit intention. Therefore, electronic word of mouth marketing is regarded as one of the ways to improve the destination sustainability. The main objective of this study is to examine the tourists’ perception on destination image toward revisit intention with the moderating impact of electronic word of mouth marketing (eWOM). This study intends to investigate the importance of destination image constructs towards the enhancement of revisit intention. Apart from this, this study also attempts to govern the moderating variable of electronic word of mouth marketing (eWOM) on the relationship between destination image and revisit intention. Subsequently, a total of 300 questionnaires were distributed to local and foreign tourists visited Mulu National Park, Gunung Gading National Park, Bako National Park, Kubah National Park and Niah National Park which situated in Sarawak, Malaysia. There are a sample of 286 respondents were collected and found usable. The data analysis was performed by SPSS Version 26.0 and WarpPLS (version 7.0) with partial least squares structural equation modeling (PLS-SEM). The results of this study have shown that four direct relationship hypotheses and two moderating relationships have been supported. Interestingly, the findings have revealed that the destination image dimensions namely, price and value, destination environment, atmosphere and quality of service have a significant positive relationship on revisit intention from local and foreign tourists’ perspective, whereas no significant impact found among natural and historical attractions, entertainment and tourism activities, and tourism infrastructure. Besides, electronic word of mouth marketing (eWOM) was found to moderate the relationship between price and value, as well as atmosphere. The results of this study provide valuable information and contribution to scholars and practitioners by providing empirical evidence on the moderating impacts of electronic word of mouth marketing (eWOM) and the effects of destination image dimensions on revisit intention in the context of ecotourism.